Decreases in Blood Pressure During Thrombectomy Are Associated With Larger Infarct Volumes and Worse Functional Outcome. Issue 7 (July 2019) - Petersen, Nils H.; Ortega-Gutierrez, Santiago; Wang, Anson; Lopez, Gloria V.; Strander, Sumita; Kodali, Sreeja; Silverman, Andrew; Zheng-Lin, Binbin; Dandapat, Sudeepta; Sansing, Lauren H.; Schindler, Joseph L.; Falcone, Guido J.; et al.
Abstract : Background and Purpose—: After large-vessel intracranial occlusion, the fate of the ischemic penumbra, and ultimately final infarct volume, largely depends on tissue perfusion. In this study, we evaluated whether blood pressure reduction and sustained relative hypotension during endovascular thrombectomy are associated with infarct progression and functional outcome. Methods—: We identified consecutive patients with large-vessel intracranial occlusion ischemic stroke who underwent mechanical thrombectomy at 2 comprehensive stroke centers. Intraprocedural mean arterial pressure (MAP) was monitored throughout the procedure. ΔMAP was calculated as the difference between admission MAP and lowest MAP during endovascular thrombectomy until recanalization. Sustained hypotension was measured as the area between admission MAP and continuous measurements of intraprocedural MAP (aMAP). Final infarct volume was measured using magnetic resonance imaging at 24 hours, and functional outcome was assessed using the modified Rankin Scale at discharge and 90 days. Associations with outcome were analyzed using linear and ordinal multivariable logistic regression. Results—: Three hundred ninety patients (mean age 71±14 years, mean National Institutes of Health Stroke Scale score of 17) were included in the study; of these, 280 (72%) achieved Thrombolysis in Cerebral Infarction 2B/3 reperfusion. Eighty-seven percent of patients experienced MAP reductions during endovascular thrombectomy (mean 31±20 mm Hg). ΔMAP was associated with greater infarct growth ( P =0.036) and final infarct volume ( P =0.035). Mean ΔMAP among patients with favorable outcomes (modified Rankin Scale score, 0–2) was 20±21 mm Hg compared with 30±24 mm Hg among patients with poor outcome ( P =0.002). In the multivariable analysis, ΔMAP was independently associated with higher (worse) modified Rankin Scale scores at discharge (adjusted odds ratio per 10 mm Hg, 1.17; 95% CI, 1.04–1.32; P =0.009) and at 90 days (adjusted odds ratio per 10 mm Hg, 1.22; 95% CI, 1.07–1.38; P =0.003). The association between aMAP and outcome was also significant at discharge ( P =0.002) and 90 days ( P =0.001). Conclusions—: Blood pressure reduction before recanalization is associated with larger infarct volumes and worse functional outcomes for patients affected by large-vessel intracranial occlusion stroke. These results underscore the importance of BP management during endovascular thrombectomy and highlight the need for further investigation of blood pressure management after large-vessel intracranial occlusion stroke. Abstract : Supplemental Digital Content is available in the text.